Narrowband Ultraviolet B Phototherapy of Early Stage Mycosis Fungoides in Korean Patients - Jang, Min Soo (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
BACKGROUND: Narrowband UVB (NBUVB) is currently used to treat early mycosis fungoides (MF). There are a number of reports on the efficacy and safety of NBUVB in Caucasians, but little data is available for Asians. OBJECTIVE: This study was designed to evaluate the effectiveness and safety of NBUVB for early stage MF in Korean patients. METHODS: We enrolled 14 patients (12 men, 2 women; age range, 10~64 years) with clinically and histologically proven MF. Three patients were stage IA, and the others were stage IB. The patients received NBUVB phototherapy three times a week. The starting dose was 70% of the minimal erythema dose and was increased in 20 percent increments if the previous treatment did not cause erythema. Clinical response, total number of treatments, total cumulative dose, duration of remission and side effects were investigated. RESULTS: Eleven of 14 patients (78.6%) achieved complete remission within a mean of 15.36±5.71 weeks (range, 5~27 weeks), 31.0±7.4 treatments (range, 16~39 treatments) and a mean cumulative UVB dose of 31.31±12.16 J/cm(2) (range, 11.4~46.8 J/cm(2)). Three of the 14 patients (21.4%) achieved a partial remission. After discontinuation of treatment, 6 of 11 patients (54.5%) with complete remission relapsed after a mean of 8.5±4.09 months. No serious adverse effects were observed except for hyperpigmentation (7/14, 50%). CONCLUSION: Our data suggest that NBUVB therapy is safe and effective for the treatment of early stage MF in Korean patients.